(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
The article highlights the economic foundations of modernizing the trade and logistics system in the agro-industrial complex, focusing on cost reduction, market expansion, and export growth.